The Impact of the COVID-19 Pandemic on the Care of Women Experiencing Abortion in a University Hospital in Brazil - Dantas, Priscilla Brenda Fonseca; Trabach, Carolina Braga; Junqueira, Aline Aparecida; Nunes, Carina Cordeiro; Veiga-Junior, Nelio Neves; Baccaro, Luiz Francisco (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective To evaluate the impact of the coronavirus disease 2019 (COVID-19) pandemic on the care of patients with miscarriage and legal termination of pregnancy in a university hospital in Brazil.Methods A cross-sectional study of women admitted for abortion due to any cause at Hospital da Mulher Prof. Dr. J. A. Pinotti of Universidade Estadual de Campinas (UNICAMP), Brazil, between July 2017 and September 2021. Dependent variables were abortion-related complications and legal interruption of pregnancy. Independent variables were prepandemic period (until February 2020) and pandemic period (from March 2020). The Cochran-Armitage test, Chi-squared test, Mann-Whitney test, and multiple logistic regression were used for statistical analysis.Results Five-hundred sixty-one women were included, 376 during the prepandemic period and 185 in the pandemic period. Most patients during pandemic were single, without comorbidities, had unplanned pregnancy, and chose to initiate contraceptive method after hospital discharge. There was no significant tendency toward changes in the number of legal interruptions or complications. Complications were associated to failure of the contraceptive method (odds ratio [OR] 2.44; 95% confidence interval [CI] 1.23–4.84), gestational age (OR 1.126; 95% CI 1.039–1.219), and preparation of the uterine cervix with misoprostol (OR 1.99; 95% CI 1.01–3.96).Conclusion There were no significant differences in duration of symptoms, transportation to the hospital, or tendency of reducing the number of legal abortions and increasing complications. The patients' profile probably reflects the impact of the pandemic on family planning.
Keywords: CLAP MUSA network; perinatal information system; population surveillance; abortion; EviSIP; COVID-19